Classroom Mindfulness Education Effects on Meditation Frequency, Stress, and Self-Regulation. (April 2020) - Strait, Julia Englund; Strait, Gerald Gill; McClain, Maryellen Brunson; Casillas, Laurel; Streich, Kristin; Harper, Kristina; Gomez, Jocelyn
This preliminary randomized controlled experiment evaluated the effects of a single classroom mindfulness educational session, versus an active contact control activity (study skills review), on college students' mindfulness meditation frequency and self-reported stress, anxiety, and self-regulation. Those in the intervention group reported marginal increases in meditation frequency, decreased stress (but not anxiety), and improved self-regulation on one of two measures. Decreased stress explained the relationship between group assignment and self-regulation improvements. We provide recommendations for future research based on study limitations, as well as implications for classroom psychology instructors.